Wacław Komar – przyczynek do biografii (lata 1909–1945) - Bagieński, Witold (Komunizm: System - Ludzie - Dokumentacja, 2023)
The life of Wacław Komar is a material for an extensive biography. An activist in the communist youth organisation; a man who carried out sentences on the Polish political police informers. He escaped from the country as a wanted man. After leaving for the Soviet Union and completing sabotage training, he became a communist activist in organisations in several European countries. When he was sent to the Spanish Civil War, he was already a distinguished member of the party. During the military operations, he gained experience as a commander and then became one of the most important people in the so-called Dąbrowszczacy community.